Brown carbon and thermal–optical analysis: A correction based on optical multi-wavelength apportionment of atmospheric aerosols. (January 2016) - Massabò, D.; Caponi, L.; Bove, M.C.; Prati, P.
Abstract: Thermo-optical analysis is widely adopted for the quantitative determination of total, TC, organic, OC and elemental, EC, Carbon in aerosol samples collected on quartz fibre filters. Nevertheless, the methodology presents several issues in particular about the artefacts related to the formation of pyrolytic carbon. It is usually neglected the uncertainty due to the possible presence of brown carbon (BrC) in the sample under analysis, i.e. the optically active fraction of OC produced by biomass burning and with characteristics intermediate between OC and EC. We introduce here a novel correction to the standard thermo-optical protocol based on the determination of the fraction of the sample absorbance due to the (possible) presence of BrC. This is achievable thanks to the coupled use of the Multi Wavelength Absorbance Analyser (MWAA) of the University of Genoa and a standard Sunset Inc. EC/OC analyser. Our correction provides a firmer OC/EC separation as well as an operative quantification of the BrC mass. The methodology has been validated against independent determination of the levoglucosan content in the same filters sent to the Sunset analysis. Corrections up to 23% in the OC and EC values, determined via the standard and new thermo-optical analysis, have been found in a set of PM10 (i.e. Particulate Matter with aerodynamic diameter less than 10 μm) samples collected wintertime at a mountain site in Northern Italy. Highlights: Aerosol absorbance due to brown carbon is measured by a multi-λ equipment. Brown carbon artifacts in thermo-optical OC/EC determination are considered. A correction methodology of the standard thermo-optical approach is introduced. A firmer EC/OC separation is obtained when aerosol samples containing brown carbon. An operative quantification of the brown carbon mass is obtained at λ = 635 nm.